Model-based assessment of biomass incorporation to mitigate nitrogen losses from arable fields in Central Europe - Rothardt, Steffen; Kage, Henning (Frontiers in Agronomy, 2023)
The combination of high post-harvest soil mineral N, low N uptake in autumn/winter and percolation causes a serious risk of N losses in common crop rotations in Central-Europe. Consequences may be eutrophication of water bodies and indirect greenhouse gas emissions. One approach to synchronize N-supply and -demand would be to control microbial immobilization induced by organic matter incorporation. In order to examine the extent to which this effect varies with different amendments in field-scale, the incorporation of crop residues of winter oilseed rape, faba beans and winter wheat were compared with the application of sawdust. Measurements were supplemented with model-derived parameters and analyzed for the impact on the autumn/winter N-dynamics. We could show that the suggested mechanism significantly reduced autumn net mineralization in top soil. As expected, the reduction was larger with increasing C:N ratio of the amendment. However, the impact on N leaching out of the reach of crop roots (>120 cm) was low. Field observations, modeling processes and a theoretical amendment assessment indicated accumulation of resistant organic matter under the given environmental conditions. Consequently, the stabilized carbon has a rather long-term effect on nutrient dynamics. In conclusion, to incorporate the preceding crop residues is still the best option to mitigate post-harvest N losses and to improve soil health with minimal crop management efforts.